Isolated tuberculous lymphadenitis presenting as bilateral buboes - Palanisamy, Arun Prasath (Indian J Sex Transm Dis AIDS, 2015)
Inguinal and femoral buboes are defined as localized enlargement of lymph nodes in the groin that are painful, and may or may not be fluctuant. We report a case of 42-year-old female who presented with bilateral inguinal swelling of 6 months duration. After a complete evaluation, she was found to be a case of isolated inguinal tuberculous lymphadenitis. There was complete resolution with standard antituberculous therapy. Isolated inguinal tuberculous lymphadenitis though a rare entity in developed countries is not uncommon in developing nations. In this era of syndromic management of sexually transmitted diseases, which carries its own pros and cons, this case report emphasizes the need to look beyond the venereal causes and calls for thorough evaluation and management.